From the Farm to the Lab: How Chicken Embryos Contribute to the Field of Teratology - Wachholz, Gabriela Elis; Rengel, Bruna Duarte; Vargesson, Neil; Fraga, Lucas Rosa (Frontiers in Genetics, 2021)
Congenital anomalies and its causes, particularly, by external factors are the aim of the field called teratology. The external factors studied by teratology are known as teratogens and can be biological or environmental factors for example, chemicals, medications, recreational drugs, environmental pollutants, physical agents (e.g. X-rays and maternal hyperthermia) and maternal metabolic conditions. Proving the teratogenicity of a factor is a difficult task requiring epidemiology studies as well as experimental teratology evidence from the use of animal models, one of which is the chicken embryo. This model in particular has the advantage of being able to follow development live and in vivo, with rapid development hatching around 21 days, is cheap and easy to manipulate and to observe development. All this allows the chicken embryo to be used in drug screening studies, teratogenic evaluation and studies of mechanisms of teratogenicity. The chicken embryo shares morphological, biochemical and genetic similarities with humans as well as mammalian species, making them ideal to ascertain the actions of teratogens, as well as screen drugs to test for their safety. Pre-clinical trials for new drugs are carried out in rodents and rabbits, however, chicken embryos have been used to screen new compounds or analogs of thalidomide as well as to investigate how some drugs can lead to congenital malformations. Indeed, the chicken embryo has proved valuable in understanding how many congenital anomalies, seen in humans, arise following teratogen exposure. The aim of this review is to highlight the role of the chicken embryo as an experimental model for studies in teratology, exploring its use in drug screening studies, phenotypic evaluation and studies of teratogenic mechanisms of action. Here, we discuss many known teratogens, that have been evaluated using the chicken embryo model including some medicines, such as, thalidomide, valproic acid; recreational drugs including alcohol; environmental influences, such as viruses, specifically ZIKV, which is a newly discovered human teratogen. In addition, we discuss how the chicken embryo has provided insight on the mechanisms of teratogenesis of many compounds and also how this impact on drug safety.